Modelling quasi-three-dimensional distribution of solar irradiance on complex terrain. (March 2022) - Liu, Wenjie; Guan, Huade; Gutiérrez-Jurado, Hugo A.; Banks, Eddie W.; He, Xinguang; Zhang, Xinping
Abstract: Solar radiation, driving land-atmosphere interactions and terrestrial carbon assimilation, varies both temporally and spatially due to surface gradient, slope aspect and vegetation shading. Here we present a double-shading transposition model (DST) for simulating temporal and spatial distribution of downwelling shortwave solar radiation. The DST model considers influences of both topographic and canopy structure on radiation transmission. It simulates sub-hourly radiation distribution on and beneath vegetation canopy for any weather conditions. The model is tested against observations at two opposite-facing slopes. The simulated above- and under-canopy radiation compares well with the observed data. The model provides a convenient and effective tool for simulating spatial and temporal variation of solar radiation on mountainous areas with vegetation cover and has great potential in ecohydrological modelling and catchment management. Highlights: A distributed solar radiation model is developed for complex vegetated terrain for all weather conditions. Shading effects from both topography and vegetation canopy are considered in the model. Model performance in simulating radiation on and beneath vegetation canopy is confirmed with one-year observations.